Active Particle Accumulation at Boundaries: A Strategy to Measure Contact Angles. Issue 11 (4th September 2017) - Simmchen, Juliane; Malgaretti, Paolo
Abstract: Wetting properties of a substrate are mostly evaluated through the contact angle of droplets on these substrates, a method that works perfectly for a broad range of cases. However, in specific cases it might be difficult to macroscopically measure the contact angle and our experiments show that the behavior of active colloids when approaching edges of liquid–solid interfaces can provide additional information. Here, we present experimental evidence and a simple, geometric model to capture this behavior. Abstract : Active Janus particles swim close to drop wedges in a similar fashion as to solid walls. This behavior adapts to the drop wedges that can be found on surfaces with different functionalizations, showing contact angles from almost 0 to more than 100 degrees. Fascinatingly, over a wide range of contact angles this behavior is reliably captured by a very simple, geometrical model.